Study on semen analysis in the evaluation of male infertility in coastal Karnataka, India - Ganiga, Pradeep; Pujeri, Shivakumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: According to current recommendation a couple has to be evaluated if they fail to achieve pregnancy within one year of unprotected regular intercourse. The current incidence of infertility is around 15% which is increasing because of various factors including delay in attaining first pregnancy. The male partner evaluation includes detailed history and examination including the sexual history and semen analysis. Observational study performed on patients with primary and secondary infertility. The detailed semen analysis evaluation done in addition to notifying brief sexual history and chronic medical ailments like diabetes. Method: After proper counselling, and obtaining consent, the patients were made to collect the semen sample in a room attached to the andrology lab. Detailed evaluation of each sample was done. Prior to this procedure, relevant information like occupation, age of the patient, duration of abstinence, coitus frequency and presence of chronic medical ailments like, diabetes mellitus and chronic hypertension were noted. Results: The study, done in a tertiary care centre in coastal Karnataka, revealed that a majority of the patients were in the age group of 25-30 years with a larger group of patients having liquefaction time of <20minutes and 25% were in the oligospermia group. Conclusions: Semen analysis is an indispensable diagnostic tool in the evaluation of the male partner of infertile couples in addition to brief sexual history and occupational history.